PENGARUH KONSENTRASI GARAM TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK TELUR ASIN BELUNTAS (Pluchea indica less)-TEH HITAM (Camelia sinensis) - Adventi, Brigita Santi; Widyawati, Paini Sri; Utomo, Adrianus Rulianto (Widya Mandala Surabaya Catholic University, 2015)
ABSTRACT Egg is one kind of high nutritious food that can be easily damaged. Salting makes the egg shelf life longer than fresh egg, otherwise the fishy smell of fresh eggs has not been reduced. Therefore additional materials such as Pluchea leaves (Pluchea indica less) and black tea (Camelia sinensis) are needed to remove the fishy smell. The experimental design was a randomized block design (RBD) single factor, with the concentration of salts consist of 7 (seven) treatments, including 25%, 30%, 35%, 40%, 45%, 50%, and positive control. Each treatment was repeated four (4) times. Parameters tested were moisture content, salinity, texture, color, and organoleptic testing (color, flavor, and aroma). The data obtained were analyzed using ANAVA test at α = 5%, which aimed to determined the presence or absence of a real difference to the parameters. If the data obtained significantly different results then Duncan's Multiple Range Test Test (DMRT) with α = 5% was used to determine the level of treatment that gave a real difference. Research showed that the using of different salt concentrations was significantly affect the albumen and yolk salinity, hardness, adhesiveness, lightness, and chroma parameters, while cohesiveness and hue parameter were only visible in albumen and organoleptic of yolk. However, different treatment in salt concentration showed no significant difference in albumen and yolk in moisture content, while cohesiveness and hue parameters didn’t have significant effect on yolk and organoleptic of albumen.